Radiographic and clinical changes of the patellar tendon after tibial plateau leveling osteotomy - Carey, K.; Aiken, S. W.; DiResta, G. R.; Herr, L. G.; Monette, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Patellar tendon thickening (PTT) and patellar tendinosis (PTS) have been discussed in the veterinary literature as a post-operative complication of tibial plateau leveling osteotomy (TPLO). The purpose of this study was to define radiographic PTT, determine the frequency of and risk factors for PTT and PTS, and describe the clinical and histopathological findings of PTS after TPLO. We hypothesized that the location of the osteotomy alters forces placed on the patellar tendon resulting in PTT or PTS. Radiographs and medical records from 83 dogs undergoing 94 TPLO procedures were retrospectively evaluated. Two months post-operatively, 19 dogs (20.2%) had a normal patellar tendon or mild PTT, 51 (54.3%) had moderate PTT, and 24 (25.5%) had severe PTT. Seven of the 24 dogs (7.4%) with severe PTT had clinical signs consistent with PTS. Only dogs with severe PTT developed PTS (p < 0.0001). The risk factors for the development of PTT include: a cranial osteotomy, a partially intact cranial cruciate ligament (CCL) in conjunction with a cranial osteotomy, and post-operative tibial tuberosity fracture. The only risk factor identified for the development of PTS was a partially intact CCL. Four dogs with PTS improved with conservative therapy and one improved with surgical treatment. Two dogs had tendon biopsies with histopathological review that showed tendon degeneration with lack of inflammation. As only the dogs with severe PTT develop PTS, a caudal osteotomy for the prevention of PTT and subsequent PTS is recommended.
Keywords: TPLO; patellar; tendonitis; thickening